Lipidomic Profiling Reveals Concerted Temporal Patterns of Functionally Related Lipids in Aedes aegypti Females Following Blood Feeding - Meng-Jia Lau; Shuai Nie; Qiong Yang; Lawrence G. Harshman; Cungui Mao; Nicholas A. Williamson; Ary A. Hoffmann (Metabolites, 2023)
We conducted a lipidomic analysis of the whole body of female Aedes aegypti mosquitoes at different time points over the course of feeding and reproduction. There were temporal biphasic increases of more than 80% of lipids identified at the time of feeding and from 16 h to 30 h post blood meal (PBM). During these two increases, the abundance of many lipids dropped while body weight remained stable, probably reflecting blood lipid digestion and the synthesis of vitellogenin in this period. A concerted temporal pattern was particularly strong at the second peak for membrane and signalling lipids such as phosphatidylethanolamine (PE), phosphatidylinositol (PI), cardiolipin (CL), hexosylceramide (HexCer) and lyso-phosphatidic acid (LPA). Lyso-glycerophospholipids showed three distinct change patterns that are functionally related: Lyso-PE and Lyso-phosphatidylcholine (LPC), which are membrane lipids, showed little change; LPA, a signalling lipid, showed a significant increase from 16 to 30 h PBM; Lyso-PI, a bioactive lipid, and both lyso-phosphatidylglycerol (LPG) and lyso-phosphatidylserine (LPS), which are bacterial membrane lipids, showed one significant increase from the time of feeding to 16 h post blood meal. The result of our study on the anautogenous insect Ae. aegypti point to specific lipids likely to be important in the reproductive process with a role in the formation and growth of ovarian follicles.